2014
DOI: 10.1007/s10792-014-0018-6
|View full text |Cite
|
Sign up to set email alerts
|

Link between retinopathy and nephropathy caused by complications of diabetes mellitus type 2

Abstract: While the correlation and chronology of appearance of diabetic nephropathy and retinopathy is well known in diabetes mellitus (DM) type 1 patients, in DM type 2 this correlation is less clear. A retrospective study including 917 patients with type 2 diabetes. Diabetic retinopathy (DR) was diagnosed based on fundus photographs taken with a non-mydriatic camera. Diabetic nephropathy (DN) was diagnosed based on urinary albumin concentration in a morning urine sample. Statistical analysis was performed with a seem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 22 publications
3
41
0
1
Order By: Relevance
“…Interestingly, data from the Diabetes Control and Complications Trial (DCCT) in T1DM demonstrated that progression of DR independently increases the risk of development of nephropathy, and also showed that the development of nephropathy increases the risk of DR progression . Although a previous study demonstrated that these two complications influence the incidence of each other, a retrospective study in T2DM demonstrated that the association between DR and diabetic nephropathy is unidirectional and that renal injury precedes retinal damage . Accordingly, several studies have shown that nephropathy is a risk factor for DR, including severe forms of retinopathy .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, data from the Diabetes Control and Complications Trial (DCCT) in T1DM demonstrated that progression of DR independently increases the risk of development of nephropathy, and also showed that the development of nephropathy increases the risk of DR progression . Although a previous study demonstrated that these two complications influence the incidence of each other, a retrospective study in T2DM demonstrated that the association between DR and diabetic nephropathy is unidirectional and that renal injury precedes retinal damage . Accordingly, several studies have shown that nephropathy is a risk factor for DR, including severe forms of retinopathy .…”
Section: Resultsmentioning
confidence: 99%
“…29,30,37 In this regard, Kotlarsky et al concluded that renal injury precedes retinal damage, but they stated that prospective studies are required to confirm this conclusion. 37 Additionally, the reviewed evidence indicates that DR correlates with declining GFR 34,48 and, specifically, that retinopathy severity at baseline is a predictor of the rate of decline of eGFR. 48 An important implication of the above findings is that close monitoring of individuals with DR for the presence of other microvascular complications, particularly albuminuria and impaired glomerular function, may help prevent progression to more serious kidney disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] However, there were still many conditions that DN was not associated with DR, and the incidence of fundus lesions was inconsistent in different studies. [1418] Characteristics of DN patients without DR are not fully clear yet.…”
Section: Discussionmentioning
confidence: 99%
“…The percentages of DR may vary from 85% for insulin-dependent patients to 58% for non-insulin-dependent patients for more than 15 years after diagnosis [20]. Dyslipidemia [21], puberty [22], pregnancy [23], diabetic nephropathy [24, 25], and obesity [26] have also been reported as risk factors for DR.…”
Section: Prevention Of Drmentioning
confidence: 99%